2021
DOI: 10.3390/ijerph18073617
|View full text |Cite
|
Sign up to set email alerts
|

Paving the Way for Outdoor Play: Examining Socio-Environmental Barriers to Community-Based Outdoor Play

Abstract: Outdoor play and independent, neighborhood activity, both linked with healthy childhood development, have declined dramatically among Western children in recent decades. This study examines how social, cultural and environmental factors may be hindering children’s outdoor and community-based play. A comprehensive survey was completed by 826 children (aged 10–13 years) and their parents from 12 schools (four each urban, suburban and rural) from a large county in Ontario, Canada. Five multilevel regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 130 publications
1
6
0
Order By: Relevance
“…Additionally, when parents have close ties with neighbors, they may be more willing to let their children interact with other neighborhood children [52]. Among adolescents, a socially cohesive neighborhood can offer parents additional monitoring and supervision [53]. Similar to children, parents/caretakers who assess their communities to be safe and supportive may be more willing to permit their adolescents to get outside and engage with others in the community [52].…”
Section: Physical and Social Neighborhood Environmentsmentioning
confidence: 99%
“…Additionally, when parents have close ties with neighbors, they may be more willing to let their children interact with other neighborhood children [52]. Among adolescents, a socially cohesive neighborhood can offer parents additional monitoring and supervision [53]. Similar to children, parents/caretakers who assess their communities to be safe and supportive may be more willing to permit their adolescents to get outside and engage with others in the community [52].…”
Section: Physical and Social Neighborhood Environmentsmentioning
confidence: 99%
“…We re-analyzed the data to test this hypothesis, and found that more time spent on outdoor play was found in children with low SES families at the 50th quantile [18.0 (6.4; 29.6)] and 75th quantile [30.0 (13.4; 46.6)] on weekdays, but not on weekends. However, the older child may have determined the frequency at which they played outdoors themselves because they have developed the ability of independent mobility, for example, going outside themselves and spending time playing outdoors around their communities ( 35 ). A systematic review found that children play outdoors more when there is less traffic, increased neighborhood greenness, and when they have access to a yard (ages 2–15 years) ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like IM, free play (FP) is an essential part of childhood development ( Loebach et al, 2021 ). Free play can occur in a private space, such as a yard, or a public space like a street, park, or school yard, either in the company of other children or alone.…”
Section: Introductionmentioning
confidence: 99%
“…While previous research has demonstrated social inequalities in children’s IM and engagement in AT and FP ( Bianchi et al, 2008 , Mutz and Albrecht, 2017 ), studies exploring the association between the socioeconomic level of neighbourhoods and children's engagement in these practices are limited, with inconsistent results ( Carver et al, 2014 , Delisle Nyström et al, 2019 , Larsen et al, 2009 , McDonald, 2008 , Veitch et al, 2007 , Ziviani et al, 2008 ). Some studies have shown that children living in lower SES neighbourhoods face greater barriers to FP and AT ( Larsen et al, 2015 , Loebach et al, 2021 , Veitch et al, 2017 ). These children may have restricted access to safe and accessible play spaces, which can limit their opportunities for unstructured play and exploration ( Larsen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%